FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN ASUPAN SERAT PENDERITA DM DI POLI PENYAKIT DALAM RSUD Dr. Hi. ABDUL MOELOEK PROVINSI LAMPUNG TAHUN 2014 - Usdeka Muliani (Jurnal Ilmiah Manuntung, 2015)
Indonesia is now facing degenerative diseases such as diabetes. From previous studies found fiber intake patients with DM is still much less than that recommended, while the fiber is very useful to control blood sugar levels in diabetic patient. The purpose of this study was to determine the factors associated with fiber intake in patients with diabetes mellitus disease in internist clinic Dr H. Abdul Moeloek Hospital Lampung 2014? The experiment was used analytic research by cross sectional approach, a sample of 48 respondents. Data were analyzed by univariate and bivariate. The study concluded  the most respondents: (1) age 46-65 years 66.7%; (2) 70.8% of the female sex; (3) sufficient knowledge of fiber 56.2% (4)  never received nutritional counseling; (7) 85.4% less fiber intake. From the results of the bivariate analysis found no relationship between gender, knowledge, attitudes, education, and nutrition counseling with fiber intake respondents. Relative levels for respondents with knowledge and attitude toward less fiber, and fiber intake respondents are less good then advice the authors need to increase cooperation between the clinic personnel in order to refer all patients with DM to nutrition clinic in order to obtain nutritional counseling. Other suggestions in order to do further research to find out why fiber intake of diabetic patients are still lacking, and the study of other factors such as psychological, social culture, physical state, and the state of nutrition associated with fiber intake in diabetic patient